Teaching and Assessing Research Competency in Social Work Education. - Lee, Mo Yee; Apgar, Dawn; Farmer, Lawrence; Kim, Suk-Hee; Jindani, Shinaz G.; Hussein, Amml (Journal of Social Work Education)
In response to the increasing demand for accountability and evidence-informed practice, the Council on Social Work Education (CSWE) Educational Policy and Accreditation Standards (EPAS) require that students in accredited programs demonstrate engagement in practice-informed research and research-informed practice. The CSWE accreditation involves the evaluation of how schools teach and assess the competencies and mandates that accredited schools meet EPAS standards. However, there is a knowledge gap in the different methods that accredited programs use to teach and assess students' research competency, as programs are given latitude on the methods and evaluations used. This study used a concurrent mixed-methods design, including reviews of 57 research course syllabi and 10 self-study documents, as well as focus group discussions with 22 instructors to understand the methods adopted by accredited undergraduate and graduate social work programs to teach and assess research competencies. Study findings describe curriculum structure, course content, pedagogical strategies, and assessment methods to meet CSWE EPAS competency standards. Additionally, diverse pedagogical approaches used to engage students in learning research competencies are presented. Implications include helpful andragogical practices, methods for assessing research competencies, alignment of professional training and licensing standards, and support for research instructors.